Formação e competências do profissional da informação na era digital - Paletta, Francisco Carlos (2021)
The understanding of Information Science as a field of study that integrates all phenomena related to the production, organization, dissemination and use of information, in the different areas of knowledge, were the objects of project study. In the research project relevant aspects for the formation of the information professional in the Digital Era were analyzed. We analyzed the Pedagogical Political Project of Brazilian Public Universities and its curricular matrix considering menus, workload, thematic axis. The context of the information society and the spread of the use of information and communication technologies demand the need for the development of minimum skills for the generation of autonomous citizens in the search for knowledge. The objective of this study is to analyze, according to the information obtained, where the training proves to be more adequate and effective for the preparation of a wellqualified information professional, for this, relevant aspects of selected national universities will be analyzed, pointing out particular characteristics of each course. The research presents exploratory and analytical methodology, with the objective of investigating, with field research in a qualitative manner, the actions that generate the informational competence in the Library and Information Science courses. As results we present some significant indicators for the formation of information professionals. One of the main challenges of education in the area of Information Science is the development of curricula that provide training in line with the challenges of the global market, while being concerned with the cultural and humanistic training of professionals working in the area, in this context where technology plays a key role in information management and knowledge production. The strategic value of education, teaching, and culture presents itself as a reference for the creation of cognitive and pedagogical models capable of dialoguing with the constant digital mutation. Advances in these fields work as a driving force of fundamental importance in the redimensioning of the role of information and knowledge in contributing to the social, economic and quality of life development of its society.